Parametric analyses of high-temperature data for aluminum alloys - Kaufman, J. G. 1931- (ASM International, 2008)
It is the objective of this book to describe the potential usefulness of parametric analyses in analyzing and extrapolating the properties of aluminum alloys at high temperatures. It is also the intent to illustrate the use of such methods by presenting a broad spectrum of high-temperature creep data for aluminum alloys generated from a single source and developed using consistent testing procedures and practices.
Keywords: Aluminum alloys.; Aluminum alloys -- Analysis.; elektronické knihy; electronic books